Ways to face rumors in the social networking site Facebook: Research thesis from the PhD thesis - السالم حمدان خضر; شبيب جاسم محمد (ALBAHITH ALALAMI, 2018)
The research deals with the subject of «ways to face rumors in the site of social networking Facebook», a research based on a doctoral thesis, as the research dealt with rumors in the most dangerous type of new media, which sites of social communication with the global community as spreading rumors of all kinds and afflicts everyone who has eyes on him Of the audience of these sites, and aims to identify the rumors on Facebook because it is one of the most popular sites in the world and the strategy of combating the rumors published by Facebook users in their personal pages and groups that organize them, as well as identify methods and methods that can be During which the face of the rumors in the said site and eliminate them to the great danger to the safety and security and stability of Iraqi society. The research is based on descriptive research and was based on a theoretical and practical framework through the design of the paper questionnaire to identify the views of the respondents about combating rumors in Iraqi society through axes prepared for this purpose. It also adopted a number of other research tools such as Arabic and translated books and books, scientific journals, studies and researches, A number of personal and public pages and groups on the Facebook site, and in order to verify the validity of the questionnaire and the validity of the categories and questions put in it has been used by the researcher a number of professors, academic arbitrators with experience .